2015
DOI: 10.17796/1053-4628-39.4.336
|View full text |Cite
|
Sign up to set email alerts
|

Dental Erosion and its Associated Factors In 11–16-Year Old School Children

Abstract: The prevalence of dental erosion was found to be low when compared to various studies done all over the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
2
11
0
1
Order By: Relevance
“…The present study confirmed this significant correlation but in the primary dentition only. In addition, the palatal surfaces of maxillary anterior teeth were found to be the only surfaces affected by very severe dental erosion which is in agreement with previous reports 6,13,29 . The reason for this localization of the most severe erosive damage has also been discussed earlier, and several factors were found to be involved including, for example, the pellicle layer which was found to be thinnest on the palatal surfaces of maxillary anterior teeth 18,30 .…”
supporting
confidence: 92%
“…The present study confirmed this significant correlation but in the primary dentition only. In addition, the palatal surfaces of maxillary anterior teeth were found to be the only surfaces affected by very severe dental erosion which is in agreement with previous reports 6,13,29 . The reason for this localization of the most severe erosive damage has also been discussed earlier, and several factors were found to be involved including, for example, the pellicle layer which was found to be thinnest on the palatal surfaces of maxillary anterior teeth 18,30 .…”
supporting
confidence: 92%
“…In the present study, the ETW prevalence of 57% was similar to previous studies conducted in Poland (59.8%), 3 Colombia (57.3%), 5 and Norway (59%), 9 but higher than most studies involving adolescents and young adults. 4,6,7,8,10 The differences among the studies could be attributed to the different methods/criteria of examination, sample size, age group, and setting. In Brazil, the previous published study including 15-19-year-old individuals found an ETW prevalence rate of 21%.…”
Section: Discussionmentioning
confidence: 99%
“…1 This is a multifactorial condition, since its presence and severity depend on several factors, such as nutrition, saliva, general diseases, and behavioral and lifestyle habits. 2 There are several studies assessing ETW among adolescents, 3,4,5,6,7,8,9,10 Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…Dental erosion affects many adults and infants (1)(2)(3). Its etiology is associated with population changes, especially those that result in a diet that includes substantial consumption of acidic foods and drinks (3)(4).…”
Section: Introductionmentioning
confidence: 99%